Simulation of liquid flow in structured packings using CFD-methods. (5th April 2023) - Bertling, R.; Hack, M.; Ausner, I.; Horschitz, B.; Wehrli, M.; Kenig, E.Y.
Highlights: Analysis of film and rivulet flow in structured packings. Investigation of the liquid-side residence time in structured packings. Implementation of a new modelling approach for the description of perforated surfaces. The model was successfully validated against experimental data. Abstract: In this work the liquid flow in structured packings was investigated using the volume-of-fluid (VoF) method. Along with the fluid dynamics, convective transport of a tracer was studied to determine the residence time. A novel approach for the consideration of surface microstructure and perforations was applied and validated using data obtained with high-resolution computer tomography. Gas-liquid interfacial area, holdup and residence time distributions were well reproduced. The model was then applied to investigate two liquid systems (water and a mixture of water and triethyleneglycol), while two types of the standard packing Sulzer Mellapak TM were explored. This allowed to evaluate the effects of liquid properties and geometric packing area on the flow.